Information Through the Lens of Safety and Security - Patrick Neal (The Journal of Intelligence, Conflict and Warfare, 2023)
On April 20, 2023, Dr. Patrick Neal, Senior Research Fellow at the Canadian Centre for Identity-Based Conflict and Vice President of Cyber Research at CASIS Vancouver, presented Information Through the Lens of Safety and Security at the April 2023 CASIS Digital Roundtable. The presentation was followed by a question-and-answer period with questions from the audience. The key points discussed were how information has shifted to shape culture, the future evolution of Public and National Safety, and transformations in technology from language analysis.